Pharmacotherapy for POAG. Individual approach - S.V. Balalin; V.P. Fokin (РМЖ "Клиническая офтальмология")
S.V. Balalin, V.P. Fokin S. Fyodorov Eye Microsurgery Federal State Institution, Volgograd branch, Volgograd, Russian Federation Glaucoma is still one of the leading causes of the blindness and low vision. According to the World Health Organization, an estimated number of glaucoma patients is 60.5 to 105 million and is growing steadily. In many highly developed countries, glaucoma accounts for 13–28% of blindness. High intraocular pressure (IOP) is the most important risk factor for glaucomatous optic neuropathy and low vision in primary open-angle glaucoma (POAG). It was demonstrated that IOP lowering to the individual tolerant level in POAG preserves vision for a long time. The paper discusses potential adoption of of the software for the calculation of tolerant IOP in POAG. Tolerant IOP calculations will help to adjust treatment in time to achieve individual IOP normal ranges, to predict glaucoma stabilization or progression as well glaucoma progression rate. The algorithm of treatment strategy for POAG is described. Key words: glaucoma, primary open-angle glaucoma, intraocular pressure, tolerant IOP, glaucomatous optic neuropathy, prostaglandin analogue, latanoprost, Trilactan. For citation: Balalin S.V., Fokin V.P. Pharmacotherapy for POAG. Individual approach. Russian Journal of Clinical Ophthalmology. 2019;19(1):43–48. About the authors: Sergey V. Balalin — MD, PhD, Head of the Scientific Department of the Volgograd branch; Viktor P. Fokin—MD, PhD, Professor, Director of the Volgograd branch. S. Fyodorov Eye Microsurgery Federal State Institution, Volgograd branch. 80, Zemlyachki str., Volgograd, 400138, Russian Federation. Contact information: Sergey V. Balalin, e-mail: s.v.balalin@gmail.com. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 23.10.2018.